x-7=-5x-13

Simple and best practice solution for x-7=-5x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-7=-5x-13 equation:



x-7=-5x-13
We move all terms to the left:
x-7-(-5x-13)=0
We get rid of parentheses
x+5x+13-7=0
We add all the numbers together, and all the variables
6x+6=0
We move all terms containing x to the left, all other terms to the right
6x=-6
x=-6/6
x=-1

See similar equations:

| 3(x+4)7x=24 | | 3x+2=-4x+9 | | Y=10x+13x-5 | | -2x+3-7x=-96 | | d-3.4=17.6 | | 7x-3/11=6 | | 7(-2x+8)=19 | | 44=x+6x+9 | | 69=4x | | 17b=3.57 | | -6(6+6x)=-108 | | 3x+4-5x=2+3x-5 | | x2+5x+6= | | 1.1+u/6=-18.1 | | 7(-2x+8)=53 | | -2z-3z=-35 | | 3x+4–5x=2+3x–5 | | 170=5x-7(-2x-8 | | 6x/2-40=200 | | x2+5x+6=0. | | 7s+4=39 | | 160=204-w | | 7x-3x+2x-x=16 | | a.a-15=4a-3a−15=4a−3 | | M2=(x+72) | | x2–9x-36=0 | | 6d-0.55=2d-0.65 | | 8(x+4)=5(x+3) | | 5p-8=1+6p-10 | | −x+3=4x−2 | | 3x^2-11=16 | | 75+n=9 |

Equations solver categories